Effective Replacement of Cement and Fine Aggregate by Copper Slag: Novel Approach - Kumar Gupta, Manish; Jain, Nitesh (International Journal of Computer Sciences and Engineering, 2020)
Copper slag is the result of copper extraction measure for example refining, which coasts on the outside of liquid metal, which gathered and discarded or utilized as one of the waste which can have a promising future in development industry as incomplete or full option of either concrete or totals. . It has a few applications like land filling, development of grating instrument, material granules, cutting devices, rail street counterbalance material, solid industry and so forth. These applications use exclusively with respect to 15-20% of copper slag created and the staying material is dropped as a waste. In order to scale back the development of copper slag and also to deliver a substitute material for sand and concrete a methodology has been done to dissect the use of copper slag in concrete for the fractional substitution of sand and concrete. This paper presents the copper slag mixture which is replacement of cement effectively. We are describing the various research ways to determine efficiency properly for replacing of proper cement by using aggregate quantity of copper slag. The various investigation justify this proposed novel approach of replacement of cement by conduction of durability test and compressive strength test performance.